2001
DOI: 10.1007/s002770000234
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DR4-Ala74β is associated with risk and poor outcome of severe aplastic anemia

Abstract: Severe aplastic anemia (SAA) is a heterogeneous hematological disorder with a high mortality. Genetic predisposition has been shown to play a role in a considerable proportion of SAA cases. For instance, the human lymphocyte antigen HLA-DR2 has been repeatedly demonstrated to be over-represented in SAA patients. In this paper, we expand on the evidence for the contribution of HLA polymorphism in the susceptibility to SAA, which was obtained using the "high-resolution" technique of HLA-DRB1 subtyping. The DRB1*… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 20 publications
0
16
1
Order By: Relevance
“…patients [7]. In our previous study, however, DR4 or DR4-Ala74␤ was not associated with disease susceptibility to AA [12].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…patients [7]. In our previous study, however, DR4 or DR4-Ala74␤ was not associated with disease susceptibility to AA [12].…”
Section: Discussionmentioning
confidence: 82%
“…HLA-DR2 and DR2 subtypes have been reported to be overrepresented among AA patients in several ethnic groups, including our recent study in Koreans [3][4][5][6][7][8][9][10][11][12]. DR2 or DR2 subtypes have also been shown to be associated with a good response to IST [3,5,6,8,10,11,13].…”
Section: Introductionmentioning
confidence: 91%
“…[7][8][9][10][11][12][13][14][15][16][17][18][19] An increased frequency of HLA-DR2 has been reported in some but not all studies. [9][10][11][12][13]16 An association with class I alleles (especially HLA-A2) has been inconsistently identified.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, reports on this aspect remain rare, and most reports have focused on the correlation between HLA and SAA [8,9,12,20]. In the current study, the susceptibility and protective genes among the nSAA, SAA and control groups were compared.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers from Turkey, South Korea, Pakistan and China found that DRB1*15 is one of the susceptibility genes of childhood AA [8,9,10,11]. Further studies revealed that DRB1*1501 is a susceptibility gene of AA [11,12,13,14,15,16]. The expression of DRB1*1501 and DRB1*1502 among AA patients is notably higher than in the general population [13].…”
Section: Discussionmentioning
confidence: 99%